A Score Based on NfL and Glial Markers May Differentiate Between Relapsing–Remitting and Progressive MS Course - Huss, André; Otto, Markus; Senel, Makbule; Ludolph, Albert C.; Abdelhak, Ahmed; Tumani, Hayrettin (Frontiers in Neurology, 2020)
Background The investigation of biomarkers in body fluids of multiple sclerosis (MS) patients allows the monitoring of different pathophysiological aspects of the disease. We previously reported elevated CSF and serum levels of glial fibrillary acidic protein (GFAP) but not neurofilament light chain (NfL) in progressive (PMS) compared to relapsing-remitting MS patients (RRMS). Objectives We analyzed the glial marker Chitinase-3-like protein 1 (CHI3L1) in the CSF and serum of PMS and RRMS patients. Furthermore, we wanted to illustrate the proportions of glial processes and axonal damage in PMS and RRMS patients. Therefore, we established a score based on CHI3L1, GFAP and NfL and compared this score between RRMS and PMS patients and its association with the EDSS. Methods For this study we included 86 MS patients (47 RRMS and 39 PMS) and 20 patients with other non-inflammatory neurological diseases (OND) as controls. NfL and GFAP levels were determined by the Single molecule array (Simoa). CHI3L1 levels were measured with classical enzyme-linked immunosorbent assay. A score was calculated based on glial to axonal markers (CHI3L1*GFAP/NfL, referred to as “Glia score”) to capture the extent of glial processes in relation to axonal damage in each individual patient. Results CHI3L1 showed higher CSF levels in PMS vs. RRMS and controls (p< 0.001 and p< 0.0001), RMS vs. controls (p< 0.01) and higher serum levels for PMS vs. RRMS (p< 0.05). The Glia score was higher in the CSF of PMS compared to RRMS patients (p< 0.0001) and in the serum of PMS patients compared to RRMS (p< 0.01). Furthermore, the Glia score and CHI3L1 in serum but not in CSF correlated with the disability as determined by EDSS in the PMS group but not in the RRMS group (Spearman ρ= 0.46 and 0.45, p= 0.003 and 0.004, respectively). Discussion Our data indicate the crucial involvement of glial mechanisms during the pathogenesis of PMS. Moreover, a calculated score may help to differentiate between PMS and RMS in the CSF and monitor disease progression in the serum of PMS patients.